Identification of novel loci for the generation of reporter mice - Rizzi, Nicoletta (Nucleic Acids Res, 2017)
Deciphering the etiology of complex pathologies at molecular level requires longitudinal studies encompassing multiple biochemical pathways (apoptosis, proliferation, inflammation, oxidative stress). In vivo imaging of current reporter animals enabled the spatio-temporal analysis of specific molecular events, however, the lack of a multiplicity of loci for the generalized and regulated expression of the integrated transgenes hampers the creation of systems for the simultaneous analysis of more than a biochemical pathways at the time. We here developed and tested an in vivo-based methodology for the identification of multiple insertional loci suitable for the generation of reliable reporter mice. The validity of the methodology was tested with the generation of novel mice useful to report on inflammation and oxidative stress.